2013
DOI: 10.1161/circinterventions.112.000062
|View full text |Cite
|
Sign up to set email alerts
|

Association of Body Mass Index With Major Cardiovascular Events and With Mortality After Percutaneous Coronary Intervention

Abstract: Background-Conflicting data exist regarding the relation between body mass index (BMI) and cardiovascular events and mortality after percutaneous coronary intervention. Methods and Results-We performed pooled analyses to evaluate the association between BMI (weight in kilograms divided by the square of the height in meters) and the risks of major cardiovascular events (defined as death from cardiovascular causes, nonfatal myocardial infarction, stent thrombosis, or stroke) and death among 23 181 patients from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
37
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 39 publications
3
37
0
Order By: Relevance
“…[3][4][5][6] Clinical studies have reported that obese patients have better clinical outcomes, especially after PCI. 7,8 The current study suggests 1 plausible explanation for the so-called obesity paradox. Even in the setting of a greater plaque burden, a larger EEM in the high-BMI group allows for the use of larger stents and larger balloons to achieve greater stent expansion and a larger minimum stent area, especially under the IVUS guidance that was used in 95% of the patients.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…[3][4][5][6] Clinical studies have reported that obese patients have better clinical outcomes, especially after PCI. 7,8 The current study suggests 1 plausible explanation for the so-called obesity paradox. Even in the setting of a greater plaque burden, a larger EEM in the high-BMI group allows for the use of larger stents and larger balloons to achieve greater stent expansion and a larger minimum stent area, especially under the IVUS guidance that was used in 95% of the patients.…”
Section: Discussionmentioning
confidence: 60%
“…1,2 Conversely, in patients with established coronary artery disease, the effect of obesity on clinical outcomes remains controversial. [3][4][5][6] Recent studies suggest that an increased body mass index (BMI) is associated with a decreased mortality and major adverse cardiac events, especially in patients who undergo percutaneous coronary intervention (PCI) 7,8 ; however, the mechanism of the so-called obesity paradox is not yet understood.Assessment of Dual Antiplatelet Therapy With DrugEluting Stents (ADAPT-DES) 9 was a large-scale, prospective, multicenter study designed to assess the relationship between platelet reactivity and other clinical and procedural variables versus subsequent stent thrombosis and other adverse clinical events in patients treated with DES. In an intravascular Background-Obesity is a cardiovascular risk factor, but the obesity paradox in patients undergoing percutaneous coronary intervention is poorly understood.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…24 Fourth, low body mass index is reportedly associated with impaired endothelial dysfunction, leading to reduced bioavailability of nitric oxide, which plays a role in the regulation of vascular tone and inhioverweight patients have a higher prevalence of coexisting conditions such as hypertension, dyslipidemia, and diabetes mellitus, and they may be more likely to receive treatment for such comorbidities than LBW patients. 22 However, the higher risk of stroke/SE in the present LBW group from the Fushimi AF Registry patients persisted after adjustment for sex, age, CHADS2 score, and OAC prescription, and also persisted after adjustment for antihypertensive agents, lipid-lowering agents, Figure 3. Kaplan-Meier curves for the incidence of stroke or systemic embolism (SE) in various subgroups during follow-up period.…”
Section: Bw and The Risk Of Strokementioning
confidence: 69%
“…Park et al . found that low BMI was associated with increased risks of major cardiovascular events and death among patients who underwent percutaneous coronary intervention [32]. Among overweight and obese older patients after non-ST-segment-elevation myocardial infarction, all-cause long-term mortality was lower than among those with normal weight [33].…”
Section: Discussionmentioning
confidence: 99%